Obligations in public philosophical discourse - Allen Alvarez; May Thorseth; Siri Granum Carson (Etikk i Praksis: Nordic Journal of Applied Ethics, 2018)
Four papers are included in this November 2018 special issue Open Section. First is by Bjørn Hofmann and Siri Granum Carson titled Filosofiens rolle i det offentlige ordskiftet: Hvordan har debatten om sorteringssamfunnet i 2017 påvirket forholdet mellom filosofi og samfunn? En innholdsanalyse (The role of philosophy in public debate - A content analysis of the debate on the "sorting society" in Norway in 2017). Second, Provokativ offentlig filosofi (Provocative Public Philosophy) by Aksel Braanen Sterri.  Third, Steinar Bøyum’s The Democratic Duty to Educate Oneself. And fourth, Jonas Jakobsen and Kjersti Fjørtoft’s In defence of moderate Inclusivism: Revisiting Rawls and Habermas.